Prognostic Value of Elevated Pre-treatment Serum CA-125 in Epithelial Ovarian Cancer: A Meta-Analysis - Wang, Qingyi; Feng, Xiaoling; Liu, Xiaofang; Zhu, Siyu (Frontiers in Oncology, 2022)
Abstract Background: CA-125 is a clinical biomarker with predictive effect on the prognosis of different cancers. Accumulating clinical studies have explored the possibility of using the pretreatment level of CA-125 to predict the prognosis of epithelial ovarian cancer (EOC). However, its value in predicting prognosis remains controversial. The aim of this meta-analysis was to assess the predictive value of pretreatment CA-125 level for prognosis in EOC patients. Methods: We searched EMBASE, Cochrane library, PubMed and Web of Science databases for studies published up to 3 December 2021 according to specific inclusion and exclusion criteria. The included clinical studies evaluated the relationship between pretreatment CA-125 level and the prognosis of ovarian cancer. Combined hazard ratios (HR) of overall survival (OS) and progression-free survival (PFS) reported in the studies were compared and analyzed using fixed-effects/random-effects models. Stability of the studies was determined by sensitivity analysis. Publication bias was assessed by Egger's and Begg's. Results: This meta-analysis included 24 studies published in 1995 - 2021 involving 10,795 EOC patients. Comprehensive analysis demonstrated that the serum level of CA-125 before treatment was significantly correlated with overall survival (OS: HR=1.66, 95%CI=1.31-2.10, p<0.001) and progression-free survival (PFS: HR=1.59, PFS: HR=1.59, 95%CI=1.44~1.76, p＜0.001). We have found that high pre-treatment serum CA125 level was correlated with poor survival rate after comparing the data in different geographic regions, FIGO stages, and treatments. Conclusion: The results in this study suggested that higher pre-treatment serum CA125 level is associated with poorer survival outcomes, which can be used as an indicator for determining the prognosis of EOC patients. Pre-treatment serum CA125 level might provide reliable basis for judging the risk of EOC disease progression.